Exploring The Values Of Local Wisdom Of The Besemah Tribe Through Guritan Culture - Supiyah Supiyah; Hudaidah Hudaidah; LR Retno Susanti (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
South Sumatra has a unique local wisdom, one of which is the Cultural Guritan the hereditary inherited or preserved by Besemah Tribe. Guritan an ancient literary form of poetry that characterized the old or classic literature that are anonymous ie without the author's name or authors. The contents of this Guritan contains many moral values, advice, custom rules, the voices of conscience and portraits of human nature, heroism, and the rest of the kingdom in the past, which can be learned by humans as the demands of life. One Besemah community effort to preserve this culture which is a way to introduce this culture to the children of both formal and non-formal as heir to the young generation of the nation of Indonesia. The focal point of this paper is tracing the local wisdom of besemah through the culture of guritan